Khūmư̄ sathān prakō̜pkān plō̜t yāsēptit dai yāngrai (Samnak Phatthanā Kanpō̜ngkan læ Kǣkhai Panhā Yāsēptit, Samnakngān Pō̜. Pō̜. Sō̜., Krasūang Yuttitham, 2006)
Prevention and control measures of narcotics use and help and treatment for those addicted to narcotics in government institutions, schools, and various organizations in Thailand.